Time Domain Simulation of Optical Amplifiers Incorporating ASE Noise Effect in WDM Photonic Systems - Liu, Cheuk Chi (Anthony) (My University, 2004)
To overcome optical signal attenuation m fiber-optic transmission system, amplifiers must be used in the optical link. However, the accompanying amplified spontaneous emission (ASE) noise in optical amplifiers becomes the major factor that impairs the amplified optical signal, thereby degrade the system performance especially in a cascaded amplifier system. This thesis aims at providing a numerical tool that simulates the noise effects when applying optical amplifiers in high-speed long haul transmission systems. A time domain model for Erbium-doped fiber amplifier (EDFA) and semiconductor optical amplifier (SOA), which is capable of handling the locally generated broadband ASE noise and multichannel signals, is developed with affordable computational complexity. Not only the averaged ASE noise contribution to gain saturation has been included in this model, but also the random nature of the ASE noise in optical amplifiers is incorporated through appropriate statistics. Other effects such as the nonuniform spatial distribution of carriers and frequency chirping are also considered in this model. This model is implemented numerically in order to examine the static and dynamic behaviors of the optical amplifiers. Various effects arising from the ASE noise are shown in signal waveforms picked up at any point along the optical link. Furthermore, the newly developed optical amplifier simulator is integrated with an existing time-domain simulation platform that has many other optical components assembled and is capable of handling point-to-point multichannel fiber-optic transmission system in arbitrary configuration. Consequently, the influence of the ASE noise on power booster, in-line amplifier, preamplifier, and the combination of them has been studied thoroughly in both single-channel and WDM fiber-optic transmission systems.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering